KEDUDUKAN TAP MPR RI DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN INDONESIA - Kemas Abdul Somad (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The formation of Act No. 12 year 2011 about the formation of Legislation and put the TAP MPR as one type of legislation is an implementation of the command section 22a NRI CONSTITUTION 1945 and fix errors of LAW No. 10 of 2004. TAP MPR can be classified as basic rules of State/cardinal rules state (staatsgrundgesetz) because it gives guidelines and guidance to the activities of the establishment of legislation but contain normative nature.The establishment of laws and regulations was the creation of legislation covering the stages of planning, drafting, discussion, endorsement or assignment, and enactment. And laws and regulations are regulations written that contains a binding legal norms in General and created or established by the institutions of the State or the competent authority via procedures specified in the legislation.In the system of governance of the country there are parts of the Government, each of which has its own tasks and functions however the overall such parts constitute an inseparable mix and work rationally. In this system of Government Indonesia subscribes to the principle of unitary State in desentralisasikan, unitary State was the Foundation of the content of the notion of autonomy, based on the evolving rules governing mechanism that became a balance between unity and autonomy demands.Keyword : Rule of Law, Constitution.